Knowledge and attitudes of dental practitioners toward children with special health needs - Catalan, Gerardo T. (2007)
Children with special needs have been reported to receive less adequate oral care due to the hesitance of most dentists to attend to the patient's oral conditions. This study determined the extent of dental services that could be rendered to these children based on the knowledge and attitudes of Filipino dentists toward their condition. The research involved 120 Filipino dentists who attended the most recent Philippine Dental Association Convention in selected regions. Using open and close-ended questionnaires, it was found that majority of the dental practitioners were knowledgeable but not equipped enough with skills in handling CHSN in a regular dental setting. It was recommended that a curriculum about CHSN management be included in dental schools.
"October 2007."
Thesis (M.A. Special Education)--University of the Philippines Diliman.
Keywords: Dentists -- Philippines -- Attitudes; Children with disabilities -- Dental care -- Philippines; Children with disabilities -- Health and hygiene -- Philippines; Children with disabilities -- Medical care -- Philippines